2019
DOI: 10.1038/s41598-018-38349-x
|View full text |Cite
|
Sign up to set email alerts
|

Microvascular flow dictates the compromise between spatial resolution and acquisition time in Ultrasound Localization Microscopy

Abstract: Medical ultrasound is a widely used diagnostic imaging technique for tissues and blood vessels. However, its spatial resolution is limited to a sub-millimeter scale. Ultrasound Localization Microscopy was recently introduced to overcome this limit and relies on subwavelength localization and tracking of microbubbles injected in the blood circulation. Yet, as microbubbles follow blood flow, long acquisition time are required to detect them in the smallest vessels, leading to long reconstruction of the microvasc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
171
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 134 publications
(178 citation statements)
references
References 26 publications
(34 reference statements)
6
171
0
1
Order By: Relevance
“…ings of other investigators 22,32 we were able to reconstruct ULM images at a < 10 µm pixel size, which may permit the localization of microvascular scale features. Most of the tissue background present in the B-mode cineloops ( Fig.…”
Section: Super-resolution Ulm Detects Capillary Blood Flow In Cam Tummentioning
confidence: 79%
“…ings of other investigators 22,32 we were able to reconstruct ULM images at a < 10 µm pixel size, which may permit the localization of microvascular scale features. Most of the tissue background present in the B-mode cineloops ( Fig.…”
Section: Super-resolution Ulm Detects Capillary Blood Flow In Cam Tummentioning
confidence: 79%
“…We posit that this MB separation technique allows for useful ULM imaging at relatively high MB concentrations and is therefore preferable to the clinically relevant solutions of MB where MB signals may be spatially overlapping. Given that Hingot et al 21 report that the long acquisition times for ULM imaging are dictated by rare MB flow events in the microvasculature, it follows that higher MB injection concentrations would allow for reduced acquisition times. We observed that MB separation improved the performance of established MB localization and tracking algorithms 7 and thereby resulted in better super-resolution images of vasculature.…”
Section: Discussionmentioning
confidence: 99%
“…The true size of a vessel should only be established with a large number of microbubble tracks, at a minimum sufficient to cover the vessel diameter. Consequently, the minimal number of tracks required to reconstruct a vessel was proposed by Hingot et al (2019) as the width of the vessel to be imaged divided by the super-resolved pixel size.…”
Section: Trackingmentioning
confidence: 99%